MODERN METHODS OF TEACHING PROGRAMMING LANGUAGES IN PROFESSIONAL EDUCATIONAL INSTITUTIONS. (Scientific journal of the Fergana State University, 2024)
This article discusses issues related to teaching programming languages ​​in vocational schools. Considering modern approaches to teaching programming, important aspects such as curriculum structure, choice of programming languages, teaching methods and student assessment are highlighted. The article focuses on the need to integrate practical projects, modern technologies and interaction with production into the educational process. Practical recommendations are given for optimizing the educational experience of students in order to prepare for the requirements of the modern labor market in the field of information technology. This article makes a valuable contribution to the field of programming teaching methodology and can serve as a basis for further research and the development of effective educational programs.